Anti-inflammatory and anticoagulant effects of polyphenol-rich extracts from Thymus atlanticus: An in vitro and in vivo study. (24th April 2020) - Khouya, Tarik; Ramchoun, Mhamed; Amrani, Souliman; Harnafi, Hicham; Rouis, Mustapha; Couchie, Dominique; Simmet, Thomas; Alem, Chakib
Abstract: Ethnopharmacological evidence: Thymus atlanticus ( TA ) is used in traditional medicine in Morocco to treat chronic inflammatory diseases, after local and oral treatment. Aim of study: This study aimed to investigate the in vitro and in vivo anti-inflammatory and anticoagulant activities of an aqueous extract (AE) and polyphenol fraction (PF) derived from TA . Materials and methods: The effect of AE and PF on monocyte chemoattractant protein-1 (MCP-1) production by naïve and LPS-stimulated peritoneal macrophages isolated from C57Bl/6 mice was assessed by ELISA assay. The effect of chronic administration of the extracts at three different doses by oral rout for 2 weeks on blood coagulation and inflammation induced by carrageenan in Wistar rats was evaluated. In addition, the in vitro anticoagulant effect was tested on blood plasma collected from healthy rats using the activated partial thromboplastin time (APTT), prothrombin time (PT) and thrombin time (TT) tests. The acute toxicity of AE was investigated. Phytochemical analysis was carried out by HPLC. Results: Analysis by HPLC indicated rosmarinic acid as the main phenolic acid in TA extracts. Compared to control macrophages, MCP-1 level was lower in medium supplemented with AE at 50 and 500 μg/mL and PF at 500 μg/mL, but higher in medium with PF at 50 μg/mL. Rosmarinic and chicoric acids, served as controls, significantly decreased MCP-1 production. Chronic oral administration of TA extracts prevented inflammation induced by carrageenan and induced a significant prolongation of blood coagulation time, in a dose dependant manner, in Wistar rats. The results of the in vitro assay showed that the coagulation time was significantly prolonged in plasma incubated with extracts in APTT, PT and TT tests. Lethal dose 50 of AE in mice was 27.90 ± 1.19 g/kg. Conclusion: This study indicated TA as an herb with anti-inflammatory and anticoagulant proprieties and supports the traditional use of this plant for the treatment of inflammatory diseases. Graphical abstract: Image 1